Molecular determinants of enhanced response to somatostatin receptor ligands after debulking in large GH‐producing adenomas. (14th March 2021) - Gil, Joan; Marques‐Pamies, Montserrat; Jordà, Mireia; Fajardo‐Montañana, Carmen; García‐Martínez, Araceli; Sampedro, Miguel; Serra, Guillermo; Salinas, Isabel; Blanco, Alberto; Valassi, Elena; Sesmilo, Gemma; Carrato, Cristina; et al.
Abstract: Objective: Large somatotrophic adenomas depict poor response to somatostatin receptor ligands (SRLs). Debulking has shown to enhance SRLs effect in some but not all cases and tumour volume reduction has been proposed as the main predictor of response. No biological studies have been performed so far in this matter. We aimed to identify molecular markers of response to SRLs after surgical debulking in GH‐secreting adenomas. Design: We performed a multicenter retrospective study. Patients: 24 patients bearing large GH‐producing tumours. Measurements: Clinical data and SRLs response both before and after surgical debulking were collected, and 21 molecular biomarkers of SRLs response were studied in tumour samples by gene expression. Results: From the 21 molecular markers studied, only two of them predicted enhanced SRLs response after surgery. Tumours with improved response to SRLs after surgical debulking showed lower levels of Ki‐67 ( MKI67, FC = 0.17 and P  = .008) and higher levels of RAR‐related orphan receptor C ( RORC) (FC = 3.1 and P  ˂ .001). When a cut‐off of no detectable expression was used for Ki‐67, the model provided a sensitivity of 100% and a specificity of 52.6% with an area under the curve of 65.8%. Using a cut‐off of 2 units of relative expression of RORC, the prediction model showed 100% of sensitivity and specificity. Conclusions: High levels of RORC and low levels of Ki‐67 identify improved SRLs response after surgical debulking in large somatotropic adenomas. To determine their expression would facilitate medical treatment decision‐making after surgery.